2020
DOI: 10.3390/agronomy10101489
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Flavonoid Profiles in Sprouts of Radiation Breeding Wheat Lines (Triticum aestivum L.)

Abstract: Wheat (Triticum aestivum Linn.; Poaceae), one of the most popular food crops worldwide, contains basic and essential nutrients and various health benefiting phytochemicals. Among them, flavonoids have attracted significant interest owing to their various health-promoting properties. In this study, 35 wheat mutant lines were developed via gamma-irradiated mutation breeding from the original cultivar. The effects of radiation breeding on the endogenous phytochemical production in the sprouts of these mutant line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The voucher specimens were deposited at the Radiation Breeding Research Center, Advanced Radiation Technology Institute, Korea Atomic Energy Research Institute. For the present study, seeds of the selected mutants (PWr1–37) were sown, germinated, and grown, together with two yellow wheat seeds (YW1 and YW2), in the same manner as previously reported ( 22 ). YW1 and PW were developed from the cross “Woori-mil (Korea RDA accession no.…”
Section: Methodsmentioning
confidence: 99%
“…The voucher specimens were deposited at the Radiation Breeding Research Center, Advanced Radiation Technology Institute, Korea Atomic Energy Research Institute. For the present study, seeds of the selected mutants (PWr1–37) were sown, germinated, and grown, together with two yellow wheat seeds (YW1 and YW2), in the same manner as previously reported ( 22 ). YW1 and PW were developed from the cross “Woori-mil (Korea RDA accession no.…”
Section: Methodsmentioning
confidence: 99%
“… 1 Identification based on expected mass signals [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. …”
Section: Figurementioning
confidence: 99%
“…Flavonoids are important components in plants. It has been reported that flavonoids have health benefits, such as anti-obesity, anti-inflammatory, anti-cardiovascular, anti-cancer and antioxidant activities ( Ah-Reum et al, 2020 ). Studies have shown that wheat sprouts have the effects of enhancing human immunity, antioxidant, anticancer and reducing the risk of chronic diseases, and these health effects were closely related to the unique phenolic substances and their antioxidant properties ( Yu & Beta, 2015 ).…”
Section: Introductionmentioning
confidence: 99%